Optimization of biodiesel production process for mixed Jatropha curcas–Ceiba pentandra biodiesel using response surface methodology. (1st May 2016) - Dharma, S.; Masjuki, H.H.; Ong, Hwai Chyuan; Sebayang, A.H.; Silitonga, A.S.; Kusumo, F.; Mahlia, T.M.I.
Graphical abstract: Highlights: Jatropha curcas and Ceiba pentandra are potential feedstock for biodiesel. Optimization of biodiesel production by response surface methodology. Jatropha curcas – Ceiba pentandra mixed biodiesel yield was 93.33%. The properties of mixed biodiesel fulfill ASTMD6751 standard. Abstract: Exploring and improvement of biodiesel production from non-edible vegetable oil is one of the effective ways to solve limited amount of traditional raw materials and their high prices. The main objective of this study is to optimize the biodiesel production process parameters (methanol-to-oil ratio, agitation speed and concentration of the potassium hydroxide catalyst) of a biodiesel derived from non-edible feedstocks, namely Jatropha curcas and Ceiba pentandra, using response surface methodology based on Box–Behnken experimental design. Based on the results, the optimum operating parameters for transesterification of the J50C50 oil mixture at 60 °C over a period of 2 h are as follows: methanol-to-oil ratio: 30%, agitation speed: 1300 rpm and catalyst concentration: 0.5 wt.%. These optimum operating parameters gives the highest yield for the J50C50 biodiesel with a value of 93.33%. The results show that there is a significant improvement in the physicochemical properties of the J50C50 biodiesel after optimization, whereby the kinematic viscosity at 40 °C, density at 15 °C, calorific value, acid value and oxidation stability is 3.950 mm 2 /s, 831.2 kg/m 3, 40.929 MJ/kg, 0.025 mg KOH/g and 10.01 h, respectively. The physicochemical properties of the optimized J50C50 biodiesel fulfill the requirements given in the ASTMD6751 andEN14214 standards.